A new control strategy for MMC under grid voltage unbalance condition. (27th March 2019) - Sun, Weisha; Cheng, Qiming; Cheng, Yinman; Tan, Fengren; Li, Tao; Chen, Lu
Summary: Modular multilevel converter (MMC) is easy to realize more voltage levels, and its structure is easy to connect back to back. It is suitable for high‐voltage direct current (HVDC) transmission system. However, the unbalance of grid voltage will seriously affect performance of HVDC transmission. The Lyapunov‐function‐based control strategy proposed in this paper can well solve the existing problems of MMC under unbalanced power grid. First of all, according to the topological structure of MMC, this paper establishes the mathematic model under the condition of grid unbalance and balance. Secondly, aiming at three different control objectives: (1) eliminate negative sequence current components and keep AC currents balance, (2) eliminate the active power double base frequency ripples, and (3) eliminate the reactive power double base frequency ripples. Then the Lyapunov‐function‐based control strategy is designed, and the circulating current control and capacitors voltage balance control are added to make the overall control strategy. Finally, the simulation of Lyapunov‐function‐based control strategy and traditional PI control strategy based on Matlab/Simulink platform is given. The validity and superiority of the Lyapunov‐function‐based control strategy are proved. And experiments on the hardware platform further verify the feasibility and correctness of the control strategy.